Changes in skeletal and dental relationship in Class II Division I malocclusion after rapid maxillary expansion: a prospective study - Baratieri,Carolina (2014)
OBJECTIVE: To assess skeletal and dental changes immediately after rapid maxillary expansion (RME) in Class II Division 1 malocclusion patients and after a retention period, using cone beam computed tomography (CBCT) imaging. METHODS: Seventeen children with Class II, Division 1 malocclusion and maxillary skeletal transverse deficiency underwent RME following the Haas protocol. CBCT were taken before treatment (T1), at the end of the active expansion phase (T2) and after a retention period of 6 months (T3). The scanned images were measured anteroposteriorly (SNA, SNB, ANB, overjet and MR) and vertically (N-ANS, ANS-Me, N-Me and overbite). RESULTS: Significant differences were identified immediately after RME as the maxilla moved forward, the mandible moved downward, overjet increased and overbite decreased. During the retention period, the maxilla relapsed backwards and the mandible was displaced forward, leaving patients with an overall increase in anterior facial height. CONCLUSION: RME treatment allowed more anterior than inferior positioning of the mandible during the retention period, thus significantly improving Class II dental relationship in 75% of the patients evaluated.